2017
DOI: 10.1371/journal.pone.0168675
|View full text |Cite
|
Sign up to set email alerts
|

Defending Against Advanced Persistent Threats Using Game-Theory

Abstract: Advanced persistent threats (APT) combine a variety of different attack forms ranging from social engineering to technical exploits. The diversity and usual stealthiness of APT turns them into a central problem of contemporary practical system security, since information on attacks, the current system status or the attacker’s incentives is often vague, uncertain and in many cases even unavailable. Game theory is a natural approach to model the conflict between the attacker and the defender, and this work inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 58 publications
0
42
0
1
Order By: Relevance
“…As an alternative to these detection methods, security game models [9], [10], [11] have provided quantitative risk management frameworks that allow the system to prepare for attacks proactively. FlipIt game [12] models the key leakage under APTs as a private takeover between the system operator and the attacker.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to these detection methods, security game models [9], [10], [11] have provided quantitative risk management frameworks that allow the system to prepare for attacks proactively. FlipIt game [12] models the key leakage under APTs as a private takeover between the system operator and the attacker.…”
Section: Introductionmentioning
confidence: 99%
“…We found that many MTD works only consider (and show) the improvement in regards to security and either assuming that it has no impact on performance or ignore that aspect altogether. We will now discuss the details [62], [65], [75], [69], [127], [100], [70], [59], [146], [61], [65], [76], [66], [91], [71], [78], [79], [80], [147] [64], [94], [143] [72], [67] [85], [7], [58], [107], [68], [131], [118], [77], [141] [105], [109], [73] Works in bold explicitly consider diversity of configurations.…”
Section: A Qualitative Evaluationmentioning
confidence: 99%
“…[62], [58], [59], [146], [61], [78], [79], [80], [94], [148], [147] [75], [69], [70], [107], [76], [71] [7], [68], [65], [66], [91], [131], [118], [143] Fig . 11: A Moving Target Defense is more effective if it considers the security and performance impacts of the system configurations, both in unison and also when placed in an ensemble of system configurations that the MTD leverages.…”
Section: A Qualitative Evaluationmentioning
confidence: 99%
See 2 more Smart Citations